TANGGUNG JAWAB GANTI RUGI PENGELOLA JASA TERHADAP KEHILANGAN DAN KERUSAKAN KENDARAAN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR: 458K/PDT.SUS-BPSK/2017) - Tatiana Imarasha; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Humans are social creatures who will always be in touch and need each other. There are ten basic rights that humans have, namely: the right to live, the right to have a family and continue offspring, the right to develop oneself, the right to obtain justice, the right to personal freedom, the right to security, the right to welfare, the right to participate in government, women's rights and finally children's rights. According to Article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia, it is stated that: The State of Indonesia is a State of Law. Based on the contents in this thesis, there is a problem, namely how the legal responsibility of parking service managers in the event of loss and damage to vehicles in the parking area (Case Study: Supreme Court Decision Number: 458K/PDT.SUS-BPSK/2017), further research objectives in this thesis To find out and analyze the form of legal responsibility for parking service managers in the event of loss and damage to vehicles in the parking area based on the case study of the Supreme Court decision number: 458K/Pdt.Sus-Bpsk/2017.